P101 Extending the Dutch Paediatric Formulary across Europe: successful development of country specific, parallel, paediatric drug formularies. Issue 6 (17th May 2019) - Van der Zanden, T; Neubert, A; Zahn, J; Wimmer, S; de Hoop, M; Rosness, T; Kjeldby-Høie, C; Teigen, A; Male, C; Rauch, E; Lagler, F; Rascher, W; et al.
Abstract : Backgrounds: As many drugs in paediatrics are used of off-label, prescribers across Europe face a lack of evidence-based dosing guidelines. The Dutch Paediatric Formulary (DPF) was developed to provide dosing guidelines based on best available evidence from registration data, investigator-initiated research, clinical experience and consensus (1). The DPF has recently joined forces with Germany, Norway and Austria aiming to develop multi-language, parallel, paediatric drug formularies based on the DPF. Methods The DPF database and ICT framework were extended to a duplicate database for Germany. The dosing guidelines were translated to German and reviewed for fit with German practice. Relevant drugs and dosing recommendations were selected and country-specific information was added to address country-specific needs. Work-sharing on content development was studied in a small pilot. Results: The German Pediatric Formulary (www.kinderformularium.de) was launched on 1 October 2018 within a German paediatric medication safety project (KiDSafe). At that time 119 of 769 drugs were reviewed and published in the German formulary.The dosing recommendations of the DPF show a good fit with German practice; i.e. adaptations were needed in less than 10% of the cases caused by differences in licensing status, national guidelines or availability of formulations. There were no differences in interpretation of evidence. Nine drugs - highly relevant for German practice, but not listed in the DPF, were added to the German formulary based on SmPC. The content work sharing was piloted by the development of a new monograph and the periodic revision of a monograph complying to the Dutch standard operating procedure by Germany. This pilot has shown the feasibility of work-sharing in developing and updating drug monographs. Conclusion: The Dutch framework has successfully been extended to the German situation. Work-sharing on the development of dosing recommendations is feasible. Similar extension to Norwegian and Austrian nation-wide formularies has started. References: van der Zanden T, De Wildt S, Liem T, Offringa M, de Hoog M. Developing a pediatric formulary for the netherlands. Arch Dis Child 2017;Apr;102(4):357–61. Disclosure(s): Tjitske van der Zanden is managing director of the Dutch Paediatric Pharmacotherapy Expertise Network; Saskia de Wildt is medical director of Dutch Paediatric Pharmacotherapy Expertise Network. The other authors have no financial disclosures relevant to this article.